1993
DOI: 10.1002/aic.690390314
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of fluidized particle behavior in liquid‐solid fluidized beds

Abstract: Liquid-solid fluidized beds have been adopted widely for catalytic liquid-phase reactions, separation and recovery of materials with ion exchange resin, adsorption, sedimentation, and wastewater treatment. Their unique features are the effective liquid-solid contact and the high rates of heat and mass transfer (Morooka et al., 1980;Muroyama et al., 1986;Kang and Kim, 1987). Nevertheless, the performance of a liquidsolid fluidized bed as a contactor or reactor is influenced appreciably by various factors, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…These methods are based on the analysis of ε G data. Other flow regime identification methods are the fractal [319], wavelet [320,321], Hurst's [322,323], spectral and nonlinear chaos [93,320,[324][325][326][327][328][329][330][331][332][333] and Kolmogorov entropy [332][333][334] approaches. Some authors have used methods based on the Shannon entropy, which measures the degree of indeterminacy in a system [335,336].…”
Section: The Flow Regimesmentioning
confidence: 99%
“…These methods are based on the analysis of ε G data. Other flow regime identification methods are the fractal [319], wavelet [320,321], Hurst's [322,323], spectral and nonlinear chaos [93,320,[324][325][326][327][328][329][330][331][332][333] and Kolmogorov entropy [332][333][334] approaches. Some authors have used methods based on the Shannon entropy, which measures the degree of indeterminacy in a system [335,336].…”
Section: The Flow Regimesmentioning
confidence: 99%
“…All of these studies demonstrated that the methodology of time-series analysis based on chaos theory can provide us with important insights into the complex hydrodynamics of gas-liquid BCs. In addition, different methods such as statistical analysis [24][25][26], power spectrum analysis [27], fractal analysis [28] and wavelet analysis [29,30] have been proposed to successfully describe the dynamic behavior of two-phase flow. None of these previous studies has been focused on the application of the nonlinear chaos analysis to local gas holdup fluctuations for the identification of zones of increased turbulence in the BC.…”
Section: Analogy Between Bubble Columns and Chaotic Systemsmentioning
confidence: 99%
“…That is, the lower value of K means the higher probability to anticipate the stable heat transport phenomena. If the temperature fluctuation signals were to be composed of two components, periodic and stochastic components, the periodic component would be more predictable than the stochastic one at the condition of relative low value of K [7,14]. Thus, it is reasonable that the heat transfer phenomena in liquid-liquid-solid fluidized beds are more stable, regular and periodic at the intermediate continuous liquid velocity, where K and Dh i attain their minima.…”
Section: Fluctuations Of Temperature and Heat Transfer Coefficientmentioning
confidence: 99%
“…In other words, the flow regime of solid particles changes from circulation to turbulent random motion at this intermediate U c or bed porosity condition. It has already been reported that the particle flow behavior is most regular and periodic at intermediate U c or bed porosity in liquid-solid and gas-liquid-solid fluidized beds [3,7,16,17].…”
Section: Fluctuations Of Temperature and Heat Transfer Coefficientmentioning
confidence: 99%